Análise da resistência a compressão simples de mistura de um solo arenoso com resíduos provenientes da construção civil em diferentes proporções - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Civil construction is one of the fastest growing branches in the world, with one consequence being the increase in the production of construction and demolition waste (RCD) generated by this activity. These wastes are often disposed of inappropriately, damaging nature and society. Thus, alternatives have been sought that seek to reuse these materials within the civil construction itself, or as an alternative to the use of other materials, such as when replacing aggregates for the production of concrete or asphalt, or as reinforcement of soils for foundations , slopes and floor bases. The present work has the objective of analyzing the behavior of the soil reinforced with different contents of residues, cement and ceramics, according to its constitution, by means of compaction and simple compression tests, in order to obtain comparative parameters between the natural soil and the mixtures made. Soil samples with 10%, 30% and 50% ratios of residuals were carried out with materials passing through the sieve of 4.8 mm, so that the comparisons could be better performed. From the analysis of the results it was possible to verify the effects caused by the addition of the residues to the natural soil, and what are the main parameters that influence these results. It was possible to verify the influence of the water absorption of the materials for the results found, since the larger the amount of residues, the greater the time required for the water to be absorbed satisfactorily.It was also possible to verify that the increase of 10% of ceramic residues generates a 32.62% increase of the resistance to simple compression in relation to the natural soil.
Keywords: Engenharia civil; Resíduos de construção; Solo reforçado; Solo arenoso; Compressão; Reciclagem; Civil engineering; Construction waste; Reinforced soil; Sandy soil; Compression; Recycling; CNPQ::ENGENHARIAS